Pendampingan Penyuluhan Metode Kolam Bioflok Kelompok Budidaya Ikan Karya Maju Ungaran - Ngatmin, Ngatmin; Oscar, Yulius; Santoso, Gunawan Budi; Suyono, Suyono; Harsono, Prijo (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The Community Service was carried out in Beji Village, East Ungaran District, which consisted of 13 RW 51 densely populated RT. Most of participant work in the private and government sectors. Some of entrepreneurs are held fish farming which are managed by the community as an additional necessity for life. To sum up, the implementation of Community Service in Beji village, sub-district East Ungaran can be concluded as follows: Community service activities in Beji Village, East Ungaran District, Semarang Regency run well so that participants gained knowledge which can be implemented. Participants were given an explanation on how to make good Biofloc pond fish food and providing tarpaulins to partners as a form of concern for developing biofloc ponds.